2014
DOI: 10.4236/ojst.2014.43023
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of 1% Chlorhexidine Gel on the Reduction of Dry Socket Occurence Following Surgical Third Molar Extraction— Pilot Study

Abstract: Aim & Objectives: The aim of this prospective pilot-study was to assess the efficacy of intra alveolar application of 1% chlorhexidine gel (CHX) on the reduction of dry socket (DS) occurrence following surgical extraction of mandibular third molars. Materials and Methods: A randomized split-mouth-design study included twenty-five patients with bilaterally impacted lower third molars (partial or full bone) requiring full thickness mucoperiastal flap reflection for extraction. Following surgical extraction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
5
2
Order By: Relevance
“…Our findings contrast with a previous study that reported a significant difference between chlorhexidine gel and warm saline rinse in preventing AO after surgical extraction of IMTM 17 . Similarly, our results differ from studies that evaluated the efficacy of chlorhexidine gel compared with placebos and other preventive formulations 16,22 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings contrast with a previous study that reported a significant difference between chlorhexidine gel and warm saline rinse in preventing AO after surgical extraction of IMTM 17 . Similarly, our results differ from studies that evaluated the efficacy of chlorhexidine gel compared with placebos and other preventive formulations 16,22 .…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown the effectiveness of chlorhexidine gel in preventing AO after transalveolar extraction of mandibular third molars 15–18 . However, these studies did not account for important confounding factors such as extraction difficulty and bone operating time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 23 records were excluded, including four RCTs that tested CHX mixed with other materials; one RCT that was not restricted to molar extraction; 16 RCTs that tested CHX dosage, administration time, or treatment period; and one RCT that used a duplicate sample. Of the remaining 23 trials, 20 were identified from the academic databases and three ( Ahmedi et al, 2014 ; Shaban et al, 2014 ; Younus et al, 2014 ) were identified through Google Scholar. The data from these 23 trials were used in analysis, and their characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the included trials compared the incidence of AO between CHX gel and a control. Of these, 11 used 0.2% CHX gel, one used 0.12% CHX gel ( Requena-Calla & Funes-Rumiche, 2016 ), and one used 1% CHX gel ( Ahmedi et al, 2014 ). These trials were analyzed in three subgroups, with the results summarized in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%